GENETIC DIVERSITY OF EXTRA-EARLY YELLOW MAIZE HYBRIDS UNDER STRIGA ENVIRONMENTS - Shaibu, Abdulwahab Saliu (FUDMA JOURNAL OF SCIENCES, 2021)
The success of any breeding program depends on the ability to determine germplasm diversity and genetic relationships among breeding materials. Genetic diversity is an invaluable aid in crop improvement. This study was carried out to determine the genetic diversity among 70 extra-early yellow maize hybrids under Striga environments. Cluster and principal component (PC) analyses were used to determine the genetic diversity of the hybrids. Data on morphological and agronomical data were collected. The experiment was set up in two locations (Abuja and Mokwa) in a randomized incomplete block design experiment with two replications. A significant difference was observed among the hybrids in all the traits studied and a significant genotype Ã— environment interaction was observed for all traits except for plant height, anthesis silking interval and Striga count at 8 and 10 WAP. The principal component reveals that the first three components account for 86% variability. PC1 gave maximum variability (43%) and was loaded with PC1 and the first four PCs can be utilized in hybridization programs. The principal component biplot reveals the relationship among traits and the distance of each variable in determining variability among hybrids. The cluster diagram reveals five distinct groups. Group IV consisted of Striga tolerant hybrids and group I consisted of susceptible hybrids. Both principal component and cluster analysis revealed the genetic diversity among the hybrids and identified genotypes that were Striga tolerant and could be selected as choice of parental materials to develop Striga resistant materials